Applying SERVQUAL model to measure online customer satisfaction in OTT services in Bangladesh - Akhand, Talal Ferdous (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.